Investigating measurements of fine particle (PM2.5) emissions from the cooking of meals and mitigating exposure using a cooker hood. (4th March 2019) - O'Leary, Catherine; de Kluizenaar, Yvonne; Jacobs, Piet; Borsboom, Wouter; Hall, Ian; Jones, Benjamin
Abstract: There is growing awareness that indoor exposure to particulate matter with diameter ≤ 2.5 μm (PM2.5 ) is associated with an increased risk of adverse health effects. Cooking is a key indoor source of PM2.5 and an activity conducted daily in most homes. Population scale models can predict occupant exposures to PM2.5, but these predictions are sensitive to the emission rates used. Reported emission rates are highly variable and are typically for the cooking of single ingredients and not full meals. Accordingly, there is a need to assess PM2.5 emissions from the cooking of complete meals. Mean PM2.5 emission rates and source strengths were measured for four complete meals. Temporal PM2.5 concentrations and particle size distributions were recorded using an optical particle counter (OPC), and gravimetric sampling was used to determine calibration factors. Mean emission rates and source strengths varied between 0.54—3.7 mg/min and 15—68 mg, respectively, with 95% confidence. Using a cooker hood ( apparent capture efficiency > 90%) and frying in non‐stick pans were found to significantly reduce emissions. OPC calibration factors varied between 1.5 and 5.0 showing that a single value cannot be used for all meals and that gravimetric sampling is necessary when measuring PM2.5 concentrations in kitchens.